Prospects for the Development of Social Innovations in The Context of The Country's Innovative Development (International Journal of Scientific Trends, 2026)
This article analyzes the theoretical and practical aspects of social innovation development within the context of the country's innovative development. The role of social innovations in the well-being of society, human capital, education, healthcare, employment, and regional development is highlighted. It also reveals the importance of digital transformation, civil society, social entrepreneurship, and management efficiency in this process. The article outlines institutional mechanisms for supporting social innovations, sources of funding, and directions for future development. As a result, it is based on the fact that social innovations are an important factor ensuring the sustainable development and competitiveness of the country.